A Major Locus on Wheat Chromosome 7B Associated With Late-Maturity α-Amylase Encodes a Putative ent-Copalyl Diphosphate Synthase - Derkx, Adinda; Baumann, Ute; Cheong, Judy; Mrva, Kolumbina; Sharma, Niharika; Pallotta, Margaret; Mares, Daryl (Frontiers in Plant Science, 2021)
Many wheat varieties have the potential to develop unacceptably high levels of α-amylase in the grains if exposed to a cool temperature shock or simply cool temperature during the early to middle stages of grain filling. This phenomenon is referred to as late maturity α-amylase (LMA). The enzyme persists in the grain until harvest and may result in wheat with a low Falling Number that does not meet receival and export specifications. Resistance to LMA is therefore a valuable target for wheat breeders and wheat industries in general. Genetic evidence implicating a locus on the long arm of chromosome 7B in variation in LMA phenotype was confirmed in this investigation. Through intensive fine-mapping an ent-copalyl diphosphate synthase (CPS), hitherto named LMA-1, was identified as the likely candidate gene associated with variation in LMA phenotype. Single Nucleotide Polymorphisms (SNPs) within the LMA-1 coding sequence of Chinese Spring, Maringa and Halberd result in either prematurely terminated or functionally altered proteins that are associated with useful levels of resistance to LMA. LMA-1 transcripts were detected in de-embryonated grain tissue from around 15 days after anthesis, several days before the synthesis of α-amylase, were low in the resistant varieties Chinese Spring and Maringa compared with LMA susceptible genotype Spica and were associated with a dramatic reduction in the concentrations of intermediates in the gibberellin biosynthesis pathway such as GA19, evidence that LMA-1 was functioning as CPS in the gibberellin biosynthesis pathway. A survey of a large cohort of Australian and International wheat varieties distinguished 9 major haplotypes at the LMA-1 locus. Generally within classes, there was notable variation for LMA phenotype and evidence for genotypes whose resistance is presumed to be due to genetic loci located elsewhere on the wheat genome. Further investigation is required to characterise the sequence of steps between LMA-1 and α-amylase synthesis as well as to gain a better understanding of the role and potential impact of other genetic loci. Diagnostic markers for sources of resistance and SNP variation reported in this study should assist breeders to deploy resistance associated with LMA-1 variants in breeding programs.